The Objectives, Strategies and Characteristics of Individual Investors in the Tehran Stock Exchange - Esfandyar, Shahmansuri; Roodposhti, Fereydon Rahnamay; Hashem, Nikoumaram; Reza, Vakilifard Hamid (The Indonesian Capital Market Review, 2017)
The present study aims to investigate and classify individual investors' objectives and strategies in the Tehran Stock Exchange. This study used two sets of data, investors' questionnaire and real data in TSE to comparing individual investors' strategies versus market strategies and used T-test, ANOVA and (LSD) to test hypotheses. Investment objectives are classified into five groups: building a financial buffer, capital growth, saving for retirement, investing as a hobby, and speculation; and three most common investment strategies are fundamental, technical and intuitive. Ultimately,t he correlation between objectives and strategies is examined with the behavioral characteristics of investors, such as risk appetite, aspiration level and overconfidence. The results show that, investors with technical strategies have higher aspiration levels and appetite for risk than other investors. In addition, Investors with overconfidence have capital growth and building financial buffer objectives, and monthly average return of the fundamental strategy is higher than other strategies.